Temporal perception in visual processing as a research tool - Zhou, Bin; Zhang, Ting; Mao, Lihua (Frontiers in Psychology, 2015)
Accumulated evidence has shown that the subjective time in the sub-second range can be altered by different factors; some are related to stimulus features such as luminance contrast and spatial frequency, others are processes like perceptual grouping and contextual modulation. These findings indicate that temporal perception uses neural signals involved in non-temporal feature processes and that perceptual organization plays an important role in shaping the experience of elapsed time. We suggest that the temporal representation of objects can be treated as a feature of objects. This new concept implies that psychological time can serve as a tool to study the principles of neural codes in the perception of objects like “reaction time”. Whereas “reaction time” usually reflects the state of transient signals crossing decision thresholds, “apparent time” in addition reveals the dynamics of sustained signals, thus providing complementary information of what has been obtained from “reaction time” studies.